Incorporating Undaria pinnatifida ((Harvey) Suringar 1873) bioactive extracts in electrospun wound dressings - Ferreira, Carolina Alexandra Marzia (2021)
Wounds are a worldwide health concern, as result of resistance to most antibiotics and inappropriate dressings. Therefore, effective treatment against bacterial infections remains a challenge, and new wound healing products with antimicrobial activity are very required. Thus, new natural products would be useful as therapeutic wounds, like, phlorotannins, since have reported antimicrobial, antioxidant, anti-inflammatory, UV-protective activities, among many others. Electrospun fibers are much appreciated in wound healing due to its similarities to the extracellular matrix. In this work, phlorotannins-enriched extracts from invasive Undaria pinnatifida ((Harvey) Suringar 1873) were produced and analyzed to incorporate into electrospun wound dressings. In the first part, a screening was performed, using different solvents and applying liquid-liquid fractionation. After the first outputs results, the extraction pipeline was optimized to produce 6 extracts (H, AQAE, AQs, E50, 100H, and E100s). Analytical procedures such as DPPH (2,2’ – Diphenyl-1-picryldydrazyl radical), FRAP (Ferric Antioxidant Power), TPC (Total Phenolic Content) and antimicrobial assays like microdilution were performed. The results suggest that there are two fractions that possibly have higher content in phlorotannins: AQAE and E100s. However, E100s has the highest antioxidant activity (114.61 mg.mol-1 for DPPH, and 6.56 mM eq. Fe II.mg-1 extract for FRAP), while AQAE shows 59.54 mg.mol-1 for DPPH and 3.49 mM eq. Fe II.mg-1 extract for FRAP. As well as TPC values with 0.47 eq. PGL.mg-1 versus 0.24 eq. PGL.mg-1 for AQAE. Concerning the antimicrobial activity, AQAE inhibits completely the Gram-positive Staphylococcus aureus, while E100s acts efficiently against overall wound Gram-negative and Gram-positives. Cellular effects were also evaluated as a proxy for in vivo safety, with no adverse results recorded. FTIR-ATR (Fourier-Transform Infrared spectroscopy with Attenuated Total Reflectance) and NMR (Nuclear Magnetic Resonance) characterization demonstrate that phlorotannins are present in E100s fraction, over AQAE. Consequently, E100s was selected to be incorporated in electrospun meshes. In the second part of the dissertation, 1 and 2 wt% of E100s extract was incorporated after parameters optimization for a solution with 14 wt% gelatin and 3.6 wt% of chitosan, 70% v/v of glacial Acetic Acid /2% v/v of triethylamine. and 4% v/v of BDDGE (1,4 – Butanonediol diglycydil ether). The ideal parameters achieved were a high tension of 20 kV, 0.2 mL.h-1 of flow rate and 12 cm from tip-to-collector. Physicochemical properties of electrospun meshes, including porosity, density, water contact angle, water absorption, and mechanical properties were analysed. Results showed that increasing the amount of phlorotannins-enriched extract influence the porosity, density, as well water uptake, due to the compact structure and owing to the hydrophilicity of phlorotannins which, resulting in better mechanical properties, delaying the enzymatic degradation and presenting a two-stages extract release effect. Thus, gelatin/chitosan electrospun meshes comprising phlorotannins-enrich extract are promising bioactive structures with potential to be used as a drug delivery system for skin tissue regeneration.